(untitled) (Research, Society and Development, 2022)
The indiscriminate and excessive use of antimicrobials directly contributes to the development of bacterial resistance, increasing treatment expenses, morbidity and mortality rates, hospitalization time, and various adverse reactions. Therefore, the study’s objective was to evaluate and quantify the consumption of antimicrobials used in the ICU of a Federal Public Hospital. Antimicrobial consumption was expressed as a defined daily dose (DDD) per 1000 patients/day. It was used in the World Health Organization (WHO) ATC/DDD classification. A total of 190 patients were admitted to the Intensive Care Unit, among which 51% were male, with a mean age of 53.4 ± 17.76 years, with the most prevalent age group being between 60 and 74 years (30.5 %). Among the diagnostic hypotheses of hospitalization, 26% were coronavirus infections. Of the hospitalized patients, 35.71% used some antimicrobial treatment, with meropenem being the most consumed (DDD 225.24). The study of the use of antimicrobials is an essential tool to guide the actions of the SCIH (Hospital Infection Control Service) that minimize microbial resistance and the indiscriminate and irrational use of these drugs and for the economic aspect. Furthermore, implementing an antimicrobial stewardship program optimizes the safe use of this important class of drugs.